Strategi Kepolisian Negara Republik Indonesia Dalam Menegakkan Hukum Penyebaran Pornografi Anak Melalui Platform Digital Berdasarkan UU ITE - Putra, Rizky Tri Yuwana; Rusmawan, Teddy (Brand Communication, 2024)
This research aims to analyze the strategies implemented by the Directorate of Cyber Crime (DITTIPIDSIBER) Bareskrim Polri Headquarters in preventing and enforcing the law against the spread of child pornography based on the Information and Electronic Transactions Law (UU ITE). The research approach used is descriptive qualitative using interview, observation and documentation study methods. The research results show that the strategy implemented by DITTIPIDSIBER includes preventive and repressive approaches. Preventive efforts include digital education and literacy for the public, collaboration with internet service providers, and monitoring online activities through digital forensic technology. Meanwhile, repressive efforts were carried out through in-depth investigations using digital tracking techniques, online disguise, and coordination with international law enforcement agencies. However, there are various challenges in implementing this strategy, such as technological limitations in detecting illegal content which continues to develop, regulations that have not fully accommodated technological changes, and low public awareness in reporting cybercrime cases.